THE DESIGN IMPROVING OF TOP NODE OF THE CURRENT COLLECTOR - Pavlychenko, M. Ye. (Science and Transport Progress, 2008)
In UrGUPS a new design of top assembly of current collector is developed allowing to improve the stability of contact pressure, to decrease the reduced mass, to lower the wear of contacting elements. The effect is achieved through the installation of third additional carriage to the top assembly.